Using Mountain Lion Habitat Selection in Management. Issue 2 (11th December 2019) - Dellinger, Justin A.; Cristescu, Bogdan; Ewanyk, Jonathan; Gammons, Daniel J.; Garcelon, David; Johnston, Phillip; Martins, Quinton; Thompson, Craig; Vickers, T. Winston; Wilmers, Christopher C.; Wittmer, Heiko U.; Torres, Steven G.
Abstract : We examined mountain lion habitat use patterns at multiple spatial scales to inform local and statewide management actions. Our approach can inform mountain lion population monitoring, prioritize habitat conservation, and mediate mountain lion‐prey interactions. ABSTRACT: Wildlife agencies are generally tasked with managing and conserving species at state and local levels simultaneously. Thus, it is necessary for wildlife agencies to understand basic ecological processes of a given species at multiple scales to aid decision making at commensurately varied spatial and behavioral scales. Mountain lions ( Puma concolor ) occur throughout California, USA, and are at the center of a variety of management and conservation issues. For example, they are genetically and demographically at risk in 1 region yet apparently stable and negatively affecting endangered species in another. Currently, no formal plan exists for mountain lions in California to deal with these diverse scenarios involving issues of local mountain lion population viability and problems related to predation of endangered species. To facilitate development of a state‐wide management and conservation plan, we quantified habitat selection by mountain lions at 2 spatial scales across the range of environmental conditions in which the species is found in California. Our analyses used location data from individuals ( n  = 263) collared across the state from 2001–2019. At the home range scale, mountain lions selected habitat to prioritize meeting energetic demands. At the within home range scale, mountain lions avoided areas of human activity. Further, our analyses revealed 165, 350–170, 085 km 2, depending on season, of suitable mountain lion habitat in California. Fifty percent of the suitable habitat was on unprotected lands and thus vulnerable to development. These habitat selection models will help in the development of a state‐wide conservation and management plan for mountain lions in California by guiding mountain lion population monitoring through time, prioritization of habitat to be conserved for maintaining demographic connectivity and gene flow, and efforts to mediate mountain lion‐prey interactions. Our work and application area will help with wildlife policy and management decisions related to depredation problems at the local scale and issues of habitat connectivity at the statewide scale. © 2019 The Wildlife Society.